2017
DOI: 10.1016/j.rboe.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Fat embolism syndrome in femoral shaft fractures: does the initial treatment make a difference?

Abstract: ObjectiveTo identify the risk factors correlated with the initial treatment performed.MethodsThis is a retrospective study involving a total of 272 patients diagnosed with femoral shaft fractures. Of the patients, 14% were kept at rest until the surgical treatment, 52% underwent external fixation, 10% received immediate definitive treatment, and 23% remained in skeletal traction (23%) until definitive treatment.ResultsThere were six cases of fat embolism syndrome (FES), which showed that polytrauma is the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…There have been previously conflicting results regarding the association of FES with fracture surgery. 32,33,36 The majority of femoral shaft fractures are treated operatively with a medullary nail. In a prospective, consecutive, nonrandomized clinical trial, Kropfl et al looked at 36 adult patients with femur fractures treated surgically with femoral nailing, separated into reamed and unreamed cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…There have been previously conflicting results regarding the association of FES with fracture surgery. 32,33,36 The majority of femoral shaft fractures are treated operatively with a medullary nail. In a prospective, consecutive, nonrandomized clinical trial, Kropfl et al looked at 36 adult patients with femur fractures treated surgically with femoral nailing, separated into reamed and unreamed cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies on these issues are rare, in patients admitted to emergency units due to trauma with rib fractures who require inpatient management in thoracic surgery clinics, FES symptoms are either not observed or very rare. Silva et al reported that of 229 cases with rib fractures, FES developed in only five (2.2%) 31. In the thoracic surgery clinic of our hospital, FES was not detected in any of the 709 patients with rib fractures monitored and treated due to trauma in 1998–2017.…”
Section: Discussionmentioning
confidence: 64%
“…Polytraumatized individuals were more likely to develop FES (5 of 6 patients). 17 There were no patients diagnosed with FES in the current investigation; however, 1 patient suffered intraoperative cardiac arrest, and FES remained in the differential as a potential etiology.…”
Section: Discussionmentioning
confidence: 65%
“…Although not reported in the investigations on skeletal traction referenced above, fat embolism syndrome (FES) is a rare event (,1-3%) associated with femur fractures. 9,12 Bezerra Silva et al 17 retrospectively studied 272 patients with femoral shaft fractures and reported 6 cases of FES. The initial treatment, which included rest, skeletal traction, external fixation, or immediate stabilization, was not associated with FES.…”
Section: Discussionmentioning
confidence: 99%